IMPACT Score for Traumatic Brain Injury: Validation of the Prognostic Tool in a Spanish Cohort. Issue 1 (January 2018) - Egea-Guerrero, Juan José; Rodríguez-Rodríguez, Ana; Gordillo-Escobar, Elena; Fernández-Delgado, Esperanza; Martínez-Roldán, Ángela; Roldán-Reina, Álvaro; Durán-Martínez, Pilar; de Vega-Ríos, Enrique; Freire-Aragón, María Dolores; Vilches-Arenas, Ángel; Murillo-Cabezas, Francisco; Quintana-Díaz, Manuel
Abstract : Background: The aim of this work was to validate the IMPACT (International Mission for Prognosis and Analysis of Clinical Trials in TBI) model in a Spanish cohort of patients with moderate-severe TBI (traumatic brain injury). Setting: Two level I neurotrauma centers. Participants: Patients admitted to these hospitals between 2011 and 2014 with a diagnosis of TBI and a Glasgow Coma Scale score of 12 or less. Design: Prospective observational study. Main Measures: We collected prospectively the clinical variables included in the IMPACT models. Outcome evaluation was prospectively done at 6-month follow-up according to the Glasgow Outcome Scale. Results: A total of 290 patients were included in the study. Forty-seven patients (16.2%) died within 6 months post-TBI, and 74 patients (25.5%) had an unfavorable outcome. The Hosmer-Lemeshow test revealed that there was no difference between observed and predicted outcomes; hence, the 3 models displayed adequate calibration for predicting 6-month mortality or unfavorable outcome. The receiver operating characteristic curve indicated that the 3 models (Core, Extended, and Lab) could accurately discriminate between favorable and unfavorable outcomes, as well as between survival and mortality ( P < .001). Conclusion: The IMPACT model validates prediction of 6-month outcomes in a Spanish population of moderate-severe TBI. IMPACT Lab model is the one that presents a higher discriminative capacity. These results encourage the implementation of the IMPACT model as a prognostic tool in the management of patients with TBI.